THE NEED TO HARMONIZE LEGAL EDUCATION AND MORAL EDUCATION IN NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
This article emphasizes that legal education and moral upbringing are a continuous process, and legal concepts should be explained to a child from kindergarten age. It is important that children be aware of the rules of conduct in the family and in preschool educational institutions, receive basic understanding of moral and some legal norms, and in the future this knowledge should be expanded and deepened to acquire a clearly expressed legal character.